O curso de pedagogia e a diversidade étnico-racial: trilhando caminhos - Bedani, Vanessa Mantovani (Universidade Federal de São Carlos, 2006)
This research aimed to comprehend the way it is and how should be the treatment of racial-ethnical diversity in Pedagogy course from professors and students point of view. This study was guided by the following research question: How racial-ethnical diversity is treated and how it should be treated in Pedagogy course regarding students and professors understanding? It focused racial-ethnical relations in Pedagogy course and attempted to place Pedagogy as a science in racial-ethnical diversity perspective. Four professors and three students of Pedagogy course from the Federal University of São Carlos took part in the research. There were conversations with trigger questions and the data analysis was organized by a summary of answers to each of the trigger questions. Data analysis showed that Pedagogy course needs to offer conditions to students, professors and others to analyze and question the racial-ethnical treatment, in order to have a theoretical-practical stance towards the racial-ethnical diversity. By means of dialog, theoretical education, reflection, commitment, awareness of the National Curricular Policies Report for the Racial-Ethnical Education and for the History Education and Afro-Brazilian Culture, discipline, among others. This study considers that Pedagogy course is not the only environment, but the central one to search, dialog, research and test the anti- racist Pedagogy allowing professors to have the possibility to reformulate their stances and practices. And they should be able to contribute, in order to educate citizens, to a society that acts with resentment in face of racism or any discrimination practice.
Keywords: Professores - formação; Diversidade étnico-racial; Educação; Relações étnicas e raciais; Pedagogia; Pedagogy; Professor s education; Racial-ethnics diversity; Racialethnics relations education; CIENCIAS HUMANAS::EDUCACAO